Efektivitas Penerapan Metode Drill Dalam Meningkatkan Kemampuan Membaca Siswa Di Madrasah Ibtidaiyah Miftahul Ulum Desa Karangsari Kecamatan Weru Kabupaten Cirebon - Eni Eni; Agus Prayitno (Jurnal IAI Bunga Bangsa Cirebon, 2020)
The ability to read is a very basic ability. But in fact the ability to read students in Madrasah Ibtidaiyah (MI) there are some who have not reached the target. This needs to be improved so that students can read fluently effectively using the Drill Method. This study aims to look at the Effectiveness of the Application of the Drill Method in Improving Students' Reading Ability. The research method used is a quantitative method Experiment with the type of Classical experimental design. Data analysis technique is to test the requirements of the analysis performed with the Data Normality Test. The results of this study are: 1) The drill method is an effective way to improve reading skills; 2) Class 1A students who do not use the drill method are less capable in reading skills. The average reading level is 7.19, the median is 7.17, the mode is 7.00, while the minimum and maximum values ​​are 6.00 and 8.00 with a total reading ability of 215.61; 3) Students in class 1 B get an average reading ability of 7.55, a median of 7.83 mode 8.00 while minimum and maximum scores of 6.50 and 8.50 with a total number of pretests of 241.51; 4) Effectiveness in learning to read, can be seen with an increasing percentage in each reading exercise; 5) The difference in reading ability between the control class and the experimental class is that the overall average is 25,9. Keywords: effectiveness; drill method; reading. Abstrak Kemampuan membaca merupakan kemampuan yang sangat mendasar. Namun kenyataanya kemampuan membaca peserta didik di Madrasah Ibtidaiyah (MI) terdapat beberapa yang belum mencapai target. Hal ini perlu diperbaiki agar peserta didik dapat membaca dengan lancar secara efektif menggunakan Metode Drill. Penelitian ini bertujuan untuk melihat Efektivitas Penerapan Metode Drill Dalam Meningkatkan Kemampuan Membaca Siswa. Metode penelitian yang digunakan yaitu metode kuantitatif Experimen dengan jenis Classical experimen design. Teknik analisis data yaitu dengan pengujian persyaratan analisis yang dilakukan dengan Uji Normalitas data. Hasil dari penelitian ini yaitu : 1) Metode drill merupakan cara yang efektif dalam meningkatkan kemampuan membaca; 2) Siswa Kelas 1A yang tidak menggunakan metode drill kurang cakap dalam kemampuan membaca. Tingkat kemampuan membacanya rata-rata sebesar 7,19, median 7,17, modus 7,00, sementara nilai minimal dan maksimal sebesar 6,00 dan 8,00 dengan jumlah total kemampuan membaca sebesar 215,61; 3) Siswa kelas 1 B memperoleh nilai rata-rata kemampuan membaca sebesar 7,55, median 7,83 modus 8,00 sementara nilai minimal dan maksimal sebesar 6,50 dan 8,50 dengan jumlah total pretes sebesar 241,51; 4) Efektivitas dalam belajar membaca, bisa dilihat dengan persentase yang terus meningkat pada setiap latihan membaca; 5) Perbedaan kemampuan membaca antara kelas kontrol dan kelas eksperimen yaitu keseluruhan rata-rata sebesar 25,9. Kata Kunci: efektivitas; metode dril; membaca.